Volleyball Lower Passing Analysis of Extracurricular Students of SMA Negeri 1 Marabahan - Sitepu, Robby Setiawan; Anggara, Norma; Perdinanto, Perdinanto (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2024)
Sharing basic volleyball passing tactics used by extracurricular students at SMA Negeri 1 Marabahan is the aim of this research. The sample for this quantitative descriptive research was twelve students of SMA Negeri 1 Marabahan who played volleyball extracurricularly. Participants are selected through a deliberate selection process taking into account several factors, one of which is their understanding of the basics of volleyball. This research uses a volleyball passing test as a data collection method. Data analysis methods consist of testing protocols, survey design, and descriptive statistics. Analysis of research data revealed that 12 students of SMA Negeri 1 Marabahan who took part in volleyball extracurriculars had poor passing abilities. This finding is based on the results of the students' lower passing test at SMAN 1 Marabahan as well as an examination of the students' basic volleyball passing skills, where the torso remains upright and the legs remain bent. Bending makes the basic volleyball passing technique less than ideal because the eyes are still not focused on the ball.